PERANCANGAN VIDEO DOKUMENTER PELESTARIAN NILAI-NILAI TRADISI DIKIE PANO KECAMATAN BONJOL KABUPATEN PASAMAN - SYNTHIA MAYOLAN, Dr. Syafwandi, M.Sn., Dr. Budiwirman, M.Pd. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Dikie Pano Tradition is one of tradition located in the District Bonjol Pasaman regency that has the uniqueness of how to play it, the lack of information and the introduction of the tradition dikie pano starts form history, the ins and outs and the uniqueness of the main factor of the authors make Video Documentary Design Conservation Tradition values Dikie Pano to provide information about the tradition dikie panoVideo documentary is one of the effective media because the delivery of information through documentary video more easily attract the target audience the purpose of the documentary video is to preserve the history of tradition dikie pano and tradition Ambiak Abuak.This design method begins by pen a collection of data consisting of the main data: in the form of observation, interviews, and documentation, while additional data in the form of studies of various theories obtained through the internet. The data analysis approach uses 5W+1H analysis (what, where, when, who, why, how) with a set of question and answers as key troubleshooting. Video documentary selected as main media and supporting media: video posters, CD Label, Cover CD, T-shirt, Totbag, Stickers, Pin.Keywords: Video Documentary, Preservation, Dikie Pano